2015
DOI: 10.1597/13-127
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinear Transformation of Z-Shaped Upper Lip Scar by Diamond-Shaped Excision in Secondary Cleft Lip Deformities: A Photogrammetric Evaluation

Abstract: Purpose : The visible Z-shaped upper lip scar that occurs after the Tennison and Randall triangular flap technique remains a cleft stigma. Herein, we present our curvilinear transformation technique for the Z-shaped upper lip scar by diamond-shaped excision and evaluate the results using photogrammetric analyses. Patients and Methods : From 1997 to 2006, 23 patients with secondary cleft lip deformity with the visible Z-shaped upper lip scar underwent correction with the technique. The scar was excised in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This procedure can be utilized in whistle deformities by pushing the vermillion inferiorly, thereby lengthening the upper lip. 3,32 When possible, this procedure is used in place of Z-plasty because it offers similar results with less scar burden. However, it is limited to correction of only small defects measuring 1 to 2 mm.…”
Section: Tissue Malpositionmentioning
confidence: 99%
“…This procedure can be utilized in whistle deformities by pushing the vermillion inferiorly, thereby lengthening the upper lip. 3,32 When possible, this procedure is used in place of Z-plasty because it offers similar results with less scar burden. However, it is limited to correction of only small defects measuring 1 to 2 mm.…”
Section: Tissue Malpositionmentioning
confidence: 99%
“…Ultimately, 32 items did not meet all of the previously set inclusion criteria. Finally, nine works met the inclusion criteria and have been included in the systematic review 11‐19 . These articles were divided according to presented cleft lip scar management methods into nonsurgical methods—4 items, and surgical methods—5 items.…”
Section: Resultsmentioning
confidence: 99%
“…They include the usage of skin flaps, grafts, and orbicularis oris muscle reconstruction. As Han et al 15 point out, the correction of cleft upper lip scarring through curvilinear transformation causes a change of shape in the scar making it narrower and less visible. Another method of correction of a post‐cleft scar is tissue graft, which replenishes upper lip tissue deficiency eliminating tension within the upper lip allowing for correction of unesthetic cleft scars 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Han et al 13 presented curvilinear transformation method for the Z-shaped upper lip scar by diamond-shaped excision and estimated the results using photogrammetric analyses, the study enrolled 23 patients with ages ranged from 8 to 35 years (mean age, 19.7 years). Of a total of 23 patients, 15 were male.…”
Section: Meta Analysismentioning
confidence: 99%
“…The mean follow-up time was 42 months. 13 As regard Outcome measures, the study by Han et al 13 reported that the width of the postoperative curvilinear scar was 4.6 6 1.6 mm. There was a statistically significant diminution between the preoperative central limb of the Z-shaped scar and the width of the postoperative curvilinear scar (P <.000) after the scar revision.…”
Section: Meta Analysismentioning
confidence: 99%